An Orientation: Past and Future (Symphony in the Flint Hills, 2016)
Introduction to the section: Since 1854, the year Kansas was opened for settlement, 6,000 of the state’s towns have disappeared.
Keywords: settlement; history never repeats itself; Jim Sherow; changing economic and technological climate; cultural changes; GOING PLACES; Risk Hazekamp